TREATMENT OF COMBINED TRAUMA COMPLICATED BY FAT EMBOLISM: EXPERIENCE OF UZBEKISTAN - Khadjibaev A. M.; Valiev E.Y. (Modern American Journals, 2025)
This article is devoted to improving the tactics of treatment of combined skeletal trauma complicated by fat embolism syndrome, which is one of the main causes of death in severe combined skeletal trauma. A single-centre study including 236 patients with combined trauma complicated by fat embolism was performed. 97 patients were in control group and received conventional therapy, 139 patients of main group undergone modern “damage control orthopedics” tactics. The authors developed and introduced into the practice of treating such patients original modern minimally invasive technologies, improved the treatment regimen for fat embolism. Modern interventions in main group significantly reduced the invasiveness and aggressiveness of interventions in patients with combined trauma and resulted in decrease of hospital stay and incidence of complications.
Keywords: Combined skeletal trauma, fat embolism, damage control orthopedics.